OPENchip: an on-chip in situ molecular profiling platform for gene expression analysis and oncogenic mutation detection in single circulating tumour cells. Issue 5 (14th February 2020) - Lee, Amos C.; Svedlund, Jessica; Darai, Evangelia; Lee, Yongju; Lee, Daewon; Lee, Han-Byoel; Kim, Sung-Min; Kim, Okju; Bae, Hyung Jong; Choi, Ahyoun; Lee, Sumin; Jeong, Yunjin; et al.
Abstract : On-chip in situ molecular profiling for gene expression analysis and oncogenic mutation detection in single circulating tumour cells is presented. Abstract : Liquid biopsy holds promise towards practical implementation of personalized theranostics of cancer. In particular, circulating tumour cells (CTCs) can provide clinically actionable information that can be directly linked to prognosis or therapy decisions. In this study, gene expression patterns and genetic mutations in single CTCs are simultaneously analysed by strategically combining microfluidic technology and in situ molecular profiling technique. Towards this, the development and demonstration of the OPENchip (On-chip Post-processing ENabling chip) platform for single CTC analysis by epithelial CTC enrichment and subsequent in situ molecular profiling is reported. For in situ molecular profiling, padlock probes that identify specific desired targets to examine biomarkers of clinical relevance in cancer diagnostics were designed and used to create libraries of rolling circle amplification products. We characterize the OPENchip in terms of its capture efficiency and capture purity, and validate the probe design using different cell lines. By integrating the obtained results, molecular analyses of CTCs from metastatic breast cancer (HER2 (ERBB2) gene expression and PIK3CA mutations) and metastatic pancreatic cancer (KRAS gene mutations) patients were demonstrated without any off-chip processes. The results substantiate the potential implementation of early molecular detection of cancer through sequencing-free liquid biopsy.